La Density as a planning tool the process of neighborhood improvement - López Borbón, Walter (Universidad Antonio Nariño, 2021)
The densities in the recent processes of planning have been more the product of the proper application effective application of rules, in an organizing principle not only of urban space, than of the occupation of the same. By groups of setters beind beyond “anonymous masses”, they are specific groups with traditions, customs and relationships that create particular forms in their social relations and in how they understand, use and transform the territory. This work seeks to establish not only a parallel between in the behavior of the densities in the urban settlements, formal and informal in origin, but explores the relationships between the characteristics of the neighborhoods, size, location, age, and size of resulting properties and densities, with the aim of reaching some conclusions and recommendations in the use and application thereof.